Morphological patterns of oblong slipmouth Photolateralis stercorarius populations in the Makassar Strait, Indonesia - MOH. TAUHID UMAR; SHARIFUDDIN BIN ANDY OMAR; FAISAL AMIR; ANDI ALIAH HIDAYANI; ANDI PARENRENGI; ABIGAIL MARY MOORE (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Umar MT, Omar SBA, Amir F, Hidayani AA, Parenrengi A, Moore AM. 2025. Morphological patterns of oblong slipmouth Photolateralis stercorarius populations in the Makassar Strait, Indonesia. Biodiversitas 26: 1675-1690. Slipmouths or ponyfishes (Leiognathidae) are important fisheries commodities in Indonesia. Morphological identification of leiognathids can be challenging, with ongoing taxonomic revisions including recent recognition of the genus Photolateralis. The purpose of this study was to describe and compare (between sites and by sex) the morphological traits of slipmouths (30 males and 30 females per site) from two sites in the Makassar Strait, South Sulawesi, Indonesia. Qualitative and quantitative (morphometric and meristic) morphological traits were recorded. Statistical analyses included Bray-Curtis dissimilarity (PAST v4.17) and discriminant analysis (XLSTAT 2019.2.2.). All specimens were identified as the oblong slipmouth P. stercorarius. The analyses showed that P. stercorarius is sexually dimorphic; males displayed a bluish longitudinal line just below the body midline, and on average females were longer than males (fork length and standard length). Meristic traits did not differ significantly by sex or between sites. Both dissimilarity and discriminant function analyses showed significant differences between the sites and between males and females at each site. The results reveal morph variation in Makassar Strait P. stercorarius populations, indicating the populations at each site may belong to a demographically separated and/or genetically distinct stock. This has implications for fisheries management, as fish stocks should be managed separately, entailing the need to determine stock boundaries.